Functionalized polyoxometalates for advanced applications - Karcher, Jeffery D. (Kansas State University, 2007)
Polyoxometalates have attracted much attention over the last few decades and have been studied in a wide variety of fields such as catalysis, medicine, imaging, photochromism, and magnetic materials. While many of these systems are easy to prepare, the ability to functionalize polyoxometalates is an ongoing challenge. Two approaches used to functionalize polyoxometalates involve insertion of metal fragments into a lacunary polyoxometalate or the direct replacement of terminal oxo ligands with the isoelectronic organoimido ligand. This process has been proven successful in many cases and with a wide variety of organoimido compounds. One of our group’s goals has been to synthesize a functionalized hexamolybdate species that is capable of metal coordination. However, previous results have been hindered because the electron withdrawing effect of the cluster is transmitted to the metal binding sites. In order to combat the electron withdrawing effect of the cluster, 4-amino piperidine dithiocarbamate ligands, which have no conjugation in the ring and are capable of metal binding, have been synthesized and characterized. A series of transition metal complexes have been made and a single crystal has been grown of a nickel(II) complex. Attempts to attach these species to clusters are described. Imido hexamolybdate clusters have been functionalized with styryl and iodophenyl groups. The styrene functionalized hexamolybdate was copolymerized with 4- chloromethylstyrene in moderate yields. This copolymer has the capabilities for further substitution at the chloromethyl group. The iodophenyl functionalized hexamolybdate was fully characterized including a single-crystal X-ray structural determination. This functionalized hexamolybdate can be used in carbon-carbon bond formation through coupling reactions. A chromium(V) nitrido polyoxometalate has been synthesized from a lacunary Keggin precursor and characterized. This nitrido species shows promise as a nitrogen transfer agent. Likewise, this nitrido species could be an entry point to other derivatives through reactions with various nucleophiles and electrophiles.
Keywords: polyoxometalates; imido ligands; molybdenum; chromium nitride; Chemistry, Inorganic (0488)